2014
DOI: 10.4187/respcare.03171
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Hospitalization Stay in COPD Exacerbations: The AECOPD-F Score

Abstract: BACKGROUND: Hospital admissions for COPD exacerbations account for 70% of total costs of COPD treatment, and the duration of hospital stay is directly related to this cost. The aim of this study was to investigate possible associations of demographic, clinical, laboratory, and functional parameters with stay of subjects admitted for COPD exacerbations and to provide a score for the prediction of the need for prolonged hospitalization. METHODS: We included 164 consecutive subjects admitted to 2 respiratory medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
1
8
0
1
Order By: Relevance
“…As outlined, we used the threshold of 7 days in line with the time when complications typically develop in an AECOPD [12]. Overall, the baseline characteristics of our AECOPD cohort were comparable to those of other studies [6, 7, 20], but we also considered variables not previously reported in this field. These included the symptom duration before admission and the use of antibiotics and the received therapy in both the short- and the long-term before hospitalisation.…”
Section: Discussionmentioning
confidence: 99%
“…As outlined, we used the threshold of 7 days in line with the time when complications typically develop in an AECOPD [12]. Overall, the baseline characteristics of our AECOPD cohort were comparable to those of other studies [6, 7, 20], but we also considered variables not previously reported in this field. These included the symptom duration before admission and the use of antibiotics and the received therapy in both the short- and the long-term before hospitalisation.…”
Section: Discussionmentioning
confidence: 99%
“…As noted above, our study findings of the association of various socio-demographic, comorbidity and hospital characteristics with COPD-hospitalization add to the current knowledge. Factors such as long term oxygen therapy, low health status, poor health related quality of life and inadequate physical activity [ 22 ] and body mass index, airflow obstruction, dyspnea, and exercise capacity (BODE) index [ 46 ] are associated with COPD hospitalization, and can predict hospital length of stay in and mortality in patients with COPD [ 47 50 ]. Our study identified additional risk factors for COPD hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with hypernatremia, defined as serum sodium levels above 145 [21], were excluded from the analysis to avoid confounding factors between high serum sodium and poor progress. Patients with prolonged stay were identified as those with a stay equal to or greater than the median stay of the study population (in our case, 7 days) [22]. Causes of death were classified into 4 groups according to origin: (1) respiratory; (2) cardiovascular (IHD, CHF, and pulmonary embolism); (3) cancer; (4) other causes (septic shock, bronchial aspiration, unknown origin, .…”
Section: Methodsmentioning
confidence: 99%